Photobiomodulation Therapy (PBMT) Applied in Bone Reconstructive Surgery Using Bovine Bone Grafts: A Systematic Review - Rosso, Marcelie Priscila de Oliveira (Materials (Basel), 2019)
The use of low-level laser therapy (LLLT) with biomodulatory effects on biological tissues, currently called photobiomodulation therapy (PBMT), assists in healing and reduces inflammation. The application of biomaterials has emerged in bone reconstructive surgery, especially the use of bovine bone due to its biocompatibility. Due to the many benefits related to the use of PBMT and bovine bones, the aim of this research was to review the literature to verify the relationship between PBMT and the application of bovine bone in bone reconstruction surgeries. We chose the PubMed/MEDLINE, Web of Science, and Scopus databases for the search by matching the keywords: “Bovine bone AND low-level laser therapy”, “Bovine bone AND photobiomodulation therapy”, “Xenograft AND low-level laser therapy”, and “Xenograft AND photobiomodulation therapy”. The initial search of the three databases retrieved 240 articles, 18 of which met all inclusion criteria. In the studies concerning animals (17 in total), there was evidence of PBMT assisting in biomaterial-related conduction, formation of new bone, bone healing, immunomarker expression, increasing collagen fibers, and local inflammation reduction. However, the results disagreed with regard to the resorption of biomaterial particles. The only human study showed that PBMT with bovine bone was effective for periodontal regeneration. It was concluded that PBMT assists the process in bone reconstruction when associated with bovine bone, despite divergences between applied protocols.